Pengaruh Modal Usaha dan Product Innovation Terhadap Eksistensi UMKM dengan Digital Marketing Sebagai Variabel Moderating Dalam Perspektif Ekonomi Islam - Fahmi Muhammad Irfan; Suharto Suharto; Hanif Hanif (Jurnal Ilmiah Ekonomi Islam, 2023)
Micro, Small and Medium Enterprises (UMKM) have a contribution to the Gross Domestic Product (GDP). This continues to increase from year to year, but has decreased during the Covid-19 pandemic. During the Covid-19 pandemic, namely in 2020-2021, all sectors experienced an economic crisis, including UMKM. The existence of the Implementation of Community Activity Restrictions (PPKM) resulted in UMKM experiencing a decrease in turnover of up to 80-90% during the co-19 pandemic. Business actors are still faced with a common problem, namely that business is hampered due to slow capital turnover, especially during the co-pandemic. Therefore, to develop UMKM Coffee Shops in Bandar Lampung, it is necessary to have additional Business Capital and Product Innovation to develop their business, accompanied by Digital Marketing as a moderation medium for the development of UMKM Coffee Shops in Bandar Lampung. Based on this, the formulation in this study is Does Business Capital have an influence on the development of UMKM in Bandar Lampung City with Digital Marketing as a Moderating Variable in the Perspective of Islamic Economics? And does Product Innovation have an influence on the development of UMKM in Bandar Lampung City with Digital Marketing as a Moderating Variable in the Perspective of Islamic Economics? The purpose of this study, to examine and analyze the effect of Business Capital on the development of UMKM in Bandar Lampung City with Digital Marketing as a Moderating Variable in an Islamic Economic Perspective and to test and analyze the effect of Product Innovation on the development of UMKM in Bandar Lampung City with Digital Marketing as a Moderating Variable in Islamic Economic Perspective. The method used in this research is a quantitative research method. The data used in this study is primary data derived from the results of the questionnaire answers that the researchers distributed to UMKM actors in the city of Bandar Lampung. The sample used uses the slovin formula with the results of the sample used by 100 UMKM actors in the city of Bandar Lampung. This study determines how much influence Business Capital has on the Development of UMKM in the City of Bandar Lampung with Digital Marketing as a moderating variable in the Islamic Economic Perspective, which is equal to 62.5%, the rest is influenced by other variables. Meanwhile, the magnitude of the influence of Product Innovation on UMKM development with digital marketing as a moderating variable is 62.4%, the rest is influenced by other variables. Most Coffee ShopUMKM have understood that product innovation is something that is needed so that a business can continue and survive.